PERAN KEPUASAN KERJA MEMEDIASI PENGARUH KECERDASAN EMOSIONAL TERHADAP KETERIKATAN KERJA: Studi Pada Perawat Wanita Instalasi Rawat Inap Rumah Sakit Umum Daerah Wangaya - Damayanti, Anak Agung Sagung Erika Rosa (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2024)
This study aims to explore the role of job satisfaction as a mediator in the relationship between emotional intelligence and work engagement, with a focus on nurses at the Wangaya Regional General Hospital. The methods that will be used are in-depth interviews and participant observation. Research subjects will be selected through purposive sampling techniques to ensure adequate representation of varying backgrounds and levels of nursing experience. The research results show that the work engagement of nurses at Wangaya Regional Hospital is not evenly distributed in each indicator, even though they tend to have good enthusiasm and appreciation in carrying out their duties. The findings also confirm the proposed hypothesis, namely that emotional intelligence has a positive and significant effect on nurses' work engagement, and that job satisfaction has a positive and significant effect on nurses' work engagement. In addition, this study found that job satisfaction mediated the relationship between emotional intelligence and nurses' work engagement.